Henkel as a Political Actor – A Strategic Response to Human Rights - Barth, Maike (2011)
Business enterprises, especially multinational corporations, are confronted with increasing institutional pressure demanding their special commitment to Human Rights. Expectations mainly arise from international NGOs as well as from the United Nations and international regulatory bodies such as the OECD or the GRI. Initial disorientation on the exact nature of these requests has been overcome through the approval of Ruggie’s “Protect, Respect & Remedy” framework for business and Human Rights by the United Nations Human Rights Council. Henkel, a German MNC from the household products sector, has an interest to develop a sophisticated and sustainable approach to confront these new expectations within its larger CSR strategy. This Management Project will investigate the international context of the Business & Human Rights debate and propose appropriate political management strategies for Henkel to confront this issue effectively. Propositions are largely based on the theoretical grounds of institutional and resource based theories.